Oxaliplatin Is a Safe Alternative Option for Patients With Recurrent Gynecologic Cancers After Hypersensitivity Reaction to Carboplatin. Issue 1 (1st January 2015) - Kolomeyevskaya, Nonna V.; Lele, Shashikant B.; Miller, Austin; Riebandt, Grazyna C.; Blum, Bonnie L.; Odunsi, Kunle O.; Frederick, Peter J.
Abstract : Objective: The aim of this study was to determine the tolerability and efficacy of oxaliplatin in patients with recurrent gynecologic malignancies after carboplatin hypersensitivity reactions in comparison with conventionally used cisplatin. Methods: Forty-six patients were treated with platinum-based chemotherapy from 2006 to 2011 and developed hypersensitivity reactions to carboplatin. Oxaliplatin was administered to 27 patients; 19 patients received cisplatin. Clinicopathologic variables, toxicity, and time-to-failure were analyzed retrospectively using descriptive statistics, Fisher exact, and independent sample permutation t tests. Results: The median number of carboplatin cycles and cumulative dose before reaction were similar in the oxaliplatin and cisplatin groups, respectively (6 vs 7.5 cycles, P = 0.93; 980 [662] mg vs 686 [579.6] mg, P = 0.49). Non–life-threatening hypersensitivity reaction to oxaliplatin developed in 2 of 27 patients. No reactions to cisplatin occurred. The median number of oxaliplatin/cisplatin cycles was 6 in both groups. Complete response to therapy was 34.6% (oxaliplatin) and 31.6% (cisplatin); stable disease was seen in 50.0% and 36.8% of oxaliplatin- and cisplatin-treated patients, respectively ( P = 0.46). Exposure to oxaliplatin resulted in less neurotoxicity than cisplatin (25.9% vs 68.4%, P = 0.01). The median number of prior chemotherapy lines in both groups was 2. The median time-to-failure was 10.8 months in oxaliplatin group and 9.8 months in cisplatin group ( P = 0.86). Conclusions: Salvage therapy with oxaliplatin after hypersensitivity reaction to carboplatin is associated with excellent tolerability and time-to-failure comparable to cisplatin. When further administration of carboplatin is precluded, oxaliplatin represents a safe and effective treatment strategy in the platinum-sensitive relapse setting. The significantly lower neurotoxicity profile makes it an attractive alternative to cisplatin.